Thulium laser vaporesection (ThuVaRP) versus bipolar transurethral resection of the prostate (TURP) in benign prostate hyperplasia in term of safety and efficacy: A two-year-follow-up study in Erbil, Iraq - Al-Bazzaz, Wishyar Jamal; Jawad, Nihad Rifaat; AlKhayat, Ali W. (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Prostate Thulium laser vaporization is a novel treatment option for a bladder outlet obstruction caused by benign prostate enlargement. However, this surgical technique has not yet been standardized. We present our finding of using Tm vaporesection of the prostate. This study aimed to assess the efficacy and safety of thulium laser versus bipolar transurethral resection of the prostate for treating patients with benign prostatic obstruction. Methods: Sixty three consecutive patients with benign prostatic hyperplasia attending public and private clinics in Erbil city were included in a comparative study from June 2014 to July 2016. Thulium laser vaporesection of the prostate was done for Group I (n = 31), and transurethral resection of the prostate was done for Group II (n = 32). All cases were evaluated preoperatively and were evaluated at 6-24 months postoperatively by international prostate symptom score, post void residual urine volume, and quality of life. Forty four patients completed the two years of follow up. Results: Thulium laser vaporization was significantly superior to bipolar plasmakinetic resection of the prostate in term of catheterization time (1.2 ± 0.7 vs 4.9 ± 1.7 days, P ≤0.001), hospital stay (1.5 ± 0.9 days vs 3.2 ± 1.6 days, P = 0.001) and drop in hemoglobin (0.8 ± 0.3 vs 2.35 ± 0.4 g/dl, P ≤0.001) and inferior to PKRP operation time (68.2 ± 27.3 vs 58.3 ± 22.7, P = 0.122). Both groups resulted in a significant improvement from baseline in terms of subjective symptoms scoring, but no significant difference was found between the two groups. Conclusion: Thulium laser vaporesection of the prostate is a safe and effective procedure for the treatment of symptomatic benign prostatic obstruction, with low perioperative morbidity however, both procedures showed no significant difference in terms of international prostate symptom score, post void residual urine volume and quality of life.